Earthquake Forces on the Stability of the Meninting Diversion Tunnel Design Based on Current Seismic Conditions of Lombok Island - Didi Supriadi Agustawijaya; Rian Mahendra Taruna; Ausa Ramadhan Agustawijaya (Indonesian Journal on Geoscience, 2022)
DOI:10.17014/ijog.9.1.105-117A series of earthquakes in 2018 have ruined thousands of buildings, and affected the stability of many infrastructures in Lombok Island. The Meninting dam, located at just a 20 km distance from the epicentre of the 5th August earthquake, is one of the many infrastructures being constructed in the island. Unfortunately, stability problems might arise to the dam, in particular to its diversion-spillway tunnel, since the tunnel was designed by using the Indonesian Standards SNI 1726:2012 for the estimation of earthquake forces into the design. After the earthquake events in 2018, seismic conditions of Lombok Island changed, resulted in changing seismic parameters. Seismic forces might shear off the friable weak volcanic rocks around the tunnel, and then consequently, the residual strength of the rocks had to stand the tunnel construction, so its factor of safety reduced. Thus, the tunnel required some stability improvements by adding more support instalments, including grouting and rock bolting. This is important for the tunnel to face probable similar severe earthquakes in the future.